Pengaruh Konsentrasi Asam Sulfat dan Waktu Reaksi Pada Sintesis α-Terpineol dari Terpentin - Prastiwi, Yohanna Francisca Budi; Selfiana, Teti; Utami, Herti (Indonesian Journal of Chemical Science, 2019)
Abstract The aim of this research is to study on  effect of the catalyst concentration of sulfuric acid (H2SO4) and reaction time in α-terpineol synthesis process from turpentine. Turpentine used in this research contents 65.891% α-pinene. Parameters that studied were the catalyst concentration of H2SO4 (20%, 25%, 30%, 35%) and reaction time (1 hour, 2 hours, 3 hours, 4 hours and 5 hours). The volume of ethanol used 135 mL. The study was carried out using a three-neck flask, a condenser, hot plate, a magnetic stirrer and thermometer with the speed stirring of 500 rpm. The product of synthesis were neutralized using 5% NaOH, then analyzed using GC and GC-MS. The results of this study showed that the highest selectivity of α-terpineol was 11,54% at 25% H2SO4 catalyst and 3 hours reaction time. Keyword : α-terpineol, α-pinene, turpentine, H2SO4